Demystifying explosives : concepts in high energy materials - Venugopalan, S. (Oxford : Elsevier, 2015)
Demystifying Explosives: Concepts in High Energy Materials explains the basic concepts of and the science behind the entire spectrum of high energy materials (HEMs) and gives a broad perspective about all types of HEMs and their interrelationships. Demystifying Explosives covers topics ranging from explosives, deflagration, detonation, and pyrotechnics to safety and security aspects of HEMS, looking at their aspects, particularly their inter-relatedness with respect to properties and performance. The book explains concepts related to the molecular structure of HEMs, their properties, performance parameters, detonation and shock waves including explosives and propellants. The theory-based title also deals with important (safety and security) and interesting (constructive applications) aspects connected with HEMs and is of fundamental use to students in their introduction to these materials and applications.
Includes index.
Description based on online resource; title from PDF title page (EBSCO, viewed February 6, 2015).
Elsevier
Keywords: Explosives; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Explosives; Electronic books